Will the Real Waleed Aly Please Stand Up? Media, Celebrity and the Making of An Australian Public Intellectual. Issue 1 (August 2015) - D'Cruz, Glenn; Weerakkody, Niranjala
Waleed Aly is arguably the most visible and vocal Australian public intellectual from a non-Anglo-Australian background. The ubiquitous Aly is a veritable Renaissance man – he is a television presenter, radio host, academic and rock musician. He is also a former lawyer, and served on the executive committee of the Islamic Council of Victoria. In short, he is the 'go-to 'Muslim for commentary on a wide range of political and civic affairs. This article argues that Aly's media profile and celebrity status have as much to do with an Australian cultural imaginary that posits 'whiteness' as an uncontestable normative value as it does with Aly's undoubted skills as a journalist, academic and cultural commentator. It examines Aly's career with reference to Ghassan Hage's concept of 'whiteness' as a form of aspirational cultural capital and various theories of persona and performativity For Hage, 'whiteness' is not a literal skin colour; rather, it consists of elements that can be adopted by individuals and groups (such as nationally valued looks, accents, tastes, cultural preferences and modes of behaviour). While entry to what Hage calls Australia's 'national aristocracy' is generally predicated on possessing the correct skin tone, it is theoretically possible for dark-skinned people such as Waleed Aly to enter the field of national belonging and partake in public discourse about a range of topical issues. More specifically, the article substantiates its claims about Aly's status as a member of Australia's cultural aristocracy through a comparative discourse and performance analysis of his presentation of 'self' in four distinctive media contexts: Channel 10's The Project, the ABC RN Drive program, ABC TV's Q&A and the SBS comedy-talk show Salaam Café, which looked at the 'funny side of life as an Australian Muslim' and showcased other multi-talented Muslim professionals of both genders.